Investigation of the Antioxidant, Antibacterial, and Antifungal Activities of Morus alba L. Fruit Extract Fractions for Potential Application in Skin Injury Treatment - Thi Thuan, Dương; Ai Nhu, Phan; Ai Nhu, Phan; Vu Kieu Giang, Nguyen; Thi Thanh, Ta (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Mulberry ( Morus alba L.), belonging to the Moraceae family, is a medicinal herb rich in polyphenolic compounds . This study was conducted to select the optimal extract fraction from mulberry fruits with antioxidant, antibacterial and antifungal activities for application in the treatment of skin lesions. An 80% ethanol extract of mulberry fruits was fractionated into n-hexane, dichloromethane (DCM), ethyl acetate (EtOAc), n-butanol, and aqueous fractions. The total polyphenol content, antioxidant capacity, antibacterial activity, and antifungal activity of the extract fractions were evaluated using the Folin-Ciocalteu method, the DPPH free-radical scavenging assay, and the agar well diffusion method, respectively. The protective effects against skin damage of gel containing the optimal extract fraction were assessed in a mouse skin model subjected to UV radiation combined with 5% NaOH-induced injury. The results showed that the EtOAc fraction had the highest total polyphenol content and the strongest antioxidant activity. The DCM fraction exhibited the most potent antibacterial activity against S. aureus , followed by the EtOAc fraction. The DCM, EtOAc, and n-butanol fractions showed comparable antifungal effects against C. albicans . Topical gel containing the EtOAc fraction demonstrated protective effects against skin damage comparable to those of the commercial product Gluta-Hya. In brief, the EtOAc fraction of mulberry presents a promising natural source of bioactive compounds for the development of topical formulations aimed at treating skin damage.